Analysis of the Effect of Job Evaluation, Workload and Competence on Employee Performance of PT Pelindo Jasa Maritim Region 4 Makassar Area: JEL Classification: M12, M54, J24, L92, D23 - Franklin Joy Agabus; A. Nur Insani; Nurmadhani Fitri Syuthi (Journal of Management and Administration Provision, 2026)
This research aims to investigate how the following variables contribute to employee performance in PT Pelindo Jasa Maritim Region 4 in Makassar: job evaluation, workload and competence. The research design utilized was a quantitative and associative research design. The sample was comprised of 67 employees of PT Pelindo Jasa Maritim Region 4. Analysis Data were analyzed with multiple linear regression with SPSS. The results show that job evaluation, workload, and competence have partially positive and statistically significant influence on the performance of the employees. Of all the variables, competence was the most significant predictor of performance. These three variables combined together explain 74.4 percent of the variance in employee performance, with the remaining 25.6 percent explained by other factors that were not considered in this study.